Analisis Pengaruh Kapitalisasi Pasar dan Harga Saham Terhadap Return Saham Pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2018-2021 - Mastiah; Erdi Rujikartawi (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
Competition in the world of business and the economy is a powerful trigger for company management to continuously improve its performance. The capital market as a medium for meeting issuers and surplus funds is an attractive option for funding and investment activities. Stocks as an investment instrument will issue returns as profits that investors can enjoy. Stocks with large capitalization are the target of investors for long-term investment, due to the company's amazing growth potential, in addition to dividend distribution and relatively low-risk exposure. In addition, a company with a high stock price is also one illustration of the value of the company which can attract investors to invest their capital. The purpose of this study is to see the effect of market capitalization and stock prices on stock returns. This type of research uses quantitative research with associative methods. The data analysis technique used is multiple linear regression analysis. The results obtained with the partial test are market capitalization has a significant positive effect on stock returns, and stock prices have a significant positive effect on stock returns. While the simultaneous test shows that market capitalization and stock prices have a significant positive effect on stock returns.